Development and characterization of GR2E Golden rice introgression lines - Swamy, B.P. Mallikarjuna; Marundan, Severino; Samia, Mercy; Ordonio, Reynante L.; Rebong, Democrito B.; Miranda, Ronalyn; Alibuyog, Anielyn; Rebong, Anna Theresa; Tabil, Ma. Angela; Suralta, Roel R.; Alfonso, Antonio A.; Biswas, Partha Sarathi; et al. (Springer, 2021)
Golden Rice with β-carotene in the grain helps to address the problem of vitamin A deficiency. Prior to commercialize Golden Rice, several performance and regulatory checkpoints must be achieved. We report results of marker assisted backcross breeding of the GR2E trait into three popular rice varieties followed by a series of confined field tests of event GR2E introgression lines to assess their agronomic performance and carotenoid expression. Results from confined tests in the Philippines and Bangladesh have shown that GR2E introgression lines matched the performance of the recurrent parents for agronomic and yield performance, and the key components of grain quality. Moreover, no differences were observed in terms of pest and disease reaction. The best performing lines identified in each genetic background had significant amounts of carotenoids in the milled grains. These lines can supply 30–50% of the estimated average requirements of vitamin A.